OPTIMIZING ENGLISH TEACHING AND LEARNING PROCESS TO YOUNG LEARNERS (A CASE STUDY IN CIMAHI) - Sri Supiyah Cahyati; Aseptiana Parmawati; Nai Supartini Atmawidjaja (Kopertis Region IV Jabar and Banten, 2019)
Having competencies on teaching English to young learners (TEYL), the teachers will be able to design materials, to teach well, and to suggest what approaches, methods, and techniques to be used. However, TEYL should not be done without careful planning and preparation. This study investigated TEYL process in Cimahi. It is intended to identify and analyze English teaching and learning process in Elementary and Kindergarten, teachers’ perception towards TEYL, and students’ responses toward English lesson. The study reported here made use of qualitative research design as its method, while the instruments were questionnaire, observations, and interview. There were 3 teachers of Kindergarten and Elementary school chosen based on purposive sampling technique as the subject of the research. e